Design of Doppler parameters estimation circuit. Issue 4 (30th May 2019) - Guo, Chenguang; Xu, Jiancheng; Zhang, Hui
Abstract : This paper designs an engineering realisation of Doppler parameters estimation circuit for synthetic aperture radar (SAR) imaging system based on motion compensation. The algorithms for Doppler centroid frequency and Doppler frequency rate estimations are selected in advance. By optimising the mapping process from algorithm to hardware circuit and selecting proper floating‐point data bit width, logical resources can be reduced significantly. Verified with an FPGA‐based PCB platform, the proposed design works properly and with controllable computing error.